KOLABORASI DALAM BERWIRAUSAHA DI DESA LUMBAN PEA TIMUR KABUPATEN TOBA - Rasmulia Sembiring; Siti Normi; Saur Melianna; Tiur Rajagukguk; Winarto Winarto; Yosephine N. Sembiring; Jhoni Maslan; Rintan Saragih; Mangasa Panjaitan; Selamat Siregar; Mislan Sihite; Jon Henri Purba; Rommel Sitohang; Veraci Silalahi (Universitas Methodist Indonesia, 2022)
Community Service aims to provide understanding and the importance of collaborating in entrepreneurship in Lumban Pea Timur Village, Toba Regency. In this case, the method used is the lecture, discussion, and question and answer method. Through this, there are many ways that can be done to collaborate in developing a business or entrepreneur. In this meeting, it is known what business is being carried out, what business will be carried out and what problems are faced in developing an entrepreneur. In the end, it was discovered that the most pressing problem in recent times is business capital and the need for a regional regulation to support and protect businesses.